(untitled) (Ibrahim Cardiac Medical Journal, 2023)
Background & objective: Preeclampsia is an age-old pregnancy-specific disorder. Numerous theories and ideas have been advanced on its etiology, pathophysiology, and complications, but commendable progress in preventing this long-standing disorder has not yet been made. The relationship between altered blood lipid levels and preeclampsia is currently a topic of discussion. The present study was to ascertain whether serum lipid levels are associated with preeclampsia. Methods: The present case-control study was carried out at the Department of Obstetrics & Gynaecology, Dhaka Medical College Hospital and Department of Obstetrics & Gynaecology, BSMMU, Dhaka over a period of one year between January 2011 to December 2011. Pregnant women in their 3rd trimester with preeclampsia were included as cases, while normal pregnant women at term without preeclampsia were included as controls. An equal number of cases (n = 75) and controls (n = 75) were selected consecutively. While the exposure variable was preeclampsia, the outcome variable was dyslipidaemia, which was defined as either total cholesterol:HDL ratio>4.5 or triglyceride:HDL ratio > 3.5. Result: The cases and the controls were almost identical in terms of age. The gestational age was also comparable between groups. The preeclamptic patients were predominantly primigravidae (57.3%) and overweight or obese (85.3%). Past history of PET was found in 12% cases as opposed to none in the controls. The prevalences of elevated serum total cholesterol (TC), LDL-C, and triglycerides (Tg) were considerably higher in the case group than those in the control group, although the differences were not statistically significant. However, the prevalence of low HDL-C was significantly higher in the former group than that in the latter group (56% vs. 14.7%, p < 0.001). The incidences of raised total cholesterol and HDL ratio > 4.5 and raised triglyceride and HDL ratio > 3.5 were observed to be significantly higher in the case group than those in the control group(p< 0.001 and p < 0.001 respectively). The likelihood of having raised TC:HDL ratio was estimated to be 10.1(95% CI = 4.2 - 23.9) times higher and that of raised TG:HDL ratio was 3.7(95% CI = 1.9 - 7.4) times higher in the case group than those in the control group. Conclusion: The total cholesterol:HDL ratio and triglyceride:HDL ratio increase significantly in preeclamptic women compared to that in normal pregnant women. However, the alteration is presumably caused by a significant lowering of HDL cholesterol, the total cholesterol and triglyceride do not experience any significant change. Ibrahim Card Med J 2022;12(2):53-58